The study of migration velocity of Cs-135 and Se-79 in intact rock. (August 2019) - Ling, H; Chen, L; Chen, W M; Yun, L
Abstract: The migration characteristics of highly mobile nuclides in natural barrier are the key concerns in the long-term safety assessment of geological disposal facilities. This paper focused on typical granite in Beishan area for geological disposal of high-level radioactive waste, and established a computational model for the release and migrate of nuclides after closure of repository by GoldSim. The migration characteristics of Cs-135 and Se-79 were analyzed by Monte Carlo stochastic simulation. The results show that the migration characteristics of Cs-135 and Se-79 in intact rock are direct influenced by hydraulic conductivity and hydraulic gradient, the migration velocity are 2.47×10 -4 m/a and 9.61×10 -4 m/a when the hydraulic conductivity correspond to 5.74 ×10 -9 m/s. The analysis of the results shows that the migration characteristics can provide feedback guidance for the site selection and design of the disposal repository.